Naringenin enhances intestinal barrier function through the expression and cytoskeletal association of tight junction proteins in Caco‐2 cells. Issue 11 (19th July 2013) - Noda, Sakino; Tanabe, Soichi; Suzuki, Takuya
<x xml:space="preserve">Abstract</x> Scope We have previously reported that naringenin promotes the tight junction (TJ) integrity in intestinal Caco‐2 cells. This study investigated the naringenin‐mediated effect in Caco‐2 cells with a particular focus on the modulation of TJ structure and claudin‐4 transcriptional regulation. Methods and results Naringenin (10∼100 μM) dose‐dependently enhanced TJ barrier integrity of Caco‐2 cells, indicated by transepithelial electrical resistance and FITC‐dextran flux. Immunoblot analysis showed that naringenin increased the cytoskeletal association of TJ proteins, zonula occludens‐2, occludin, claudin‐1, and claudin‐4, simultaneously with increased occludin phosphorylation. The total expression of claudin‐4 was also increased by naringenin. Quantitative RT‐PCR and luciferase reporter assay revealed that naringenin transcriptionally increased the claudin‐4 expression with activation of claudin‐4 promoter. The mutation of the binding site of the transcriptional factor Sp1 in the claudin‐4 promoter sequence and the pharmacological inhibition of Sp1 partially suppressed the naringenin‐mediated activation of the claudin‐4 promoter. Further, naringenin induced the heat shock protein 70 expression in the cells. Conclusion Naringenin enhances barrier integrity through the assembly and expression of TJ proteins in intestinal epithelial cells. Naringenin‐mediated claudin‐4 expression occurs, at least partially, through Sp1‐dependent transcriptional regulation. The induction of heat shock protein 70 may be also involved in the increased claudin‐4 expression.